Dictionary of World Biography - Jones, Barry (ANU Press, 2019)
Jones, Barry Owen (1932- ). Australian politician, writer and lawyer, born in Geelong. Educated at Melbourne University, he was a public servant, high school teacher, television and radio performer, university lecturer and lawyer before serving as a Labor MP in the Victorian Parliament 1972-77 and the Australian House of Representatives 1977-98. He took a leading role in reviving the Australian film industry, abolishing the death penalty in Australia, and was the first politician to raise public awareness of global warming, the 'post-industrial' society, the IT revolution, biotechnology, the rise of 'the Third Age' and the need to preserve Antarctica as a wilderness. In the Hawke Government, he was Minister for Science 1983-90, Prices and Consumer Affairs 1987, Small Business 1987-90 and Customs 1988-90. He became a member of the Executive Board of UNESCO, Paris 1991-95 and National President of the Australian Labor Party 1992-2000, 2005-06. He was Deputy Chairman of the Constitutional Convention 1998. His books include Decades of Decision 1860- (1965), Joseph II (1968), Age of Apocalypse (1975), and he edited The Penalty is Death (1968). Sleepers, Wake!: Technology and the Future of Work was published by Oxford University Press in 1982, became a bestseller and has been translated into Chinese, Japanese, Korean, Swedish and braille. The fourth edition was published in 1995. Knowledge Courage Leadership, a collection of speeches and essays, appeared in 2016. He received a DSc for his services to science in 1988 and a DLitt in 1993 for his work on information theory. Elected FTSE (1992), FAHA (1993), FAA (1996) and FASSA (2003), he is the only person to have become a Fellow of four of Australia's five learned Academies. Awarded an AO in 1993, named as one of Australia's 100 'living national treasures' in 1998, he was elected a Visiting Fellow Commoner of Trinity College, Cambridge in 1999. His autobiography, A Thinking Reed, was published in 2006 and The Shock of Recognition, about music and literature, in 2016. In 2014 he received an AC for services 'as a leading intellectual in Australian public life.